Teaching Module for Pancasila Student Profile Integrated Project-Based Learning: A Focus on Social Arithmetic Material for Middle School Students - Datunsolang, Abd. Rahman; Tiro, M. Arif; Rosidah, Rosidah (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The study's intent is to find out about the Pancasila student profile strengthening project module based on project-based learning on social arithmetic material and to explain how it was made, what its prototype looked like, how valid it was, how practical it was, and how effective it was. This research involves developing a 4D model with four stages: defining, designing, developing, and disseminating. The subjects of this study were mathematics teachers and students at Public Middle School 33 and Public Middle School 6 in Makassar. The study's results show that (1) at the definition stage, it was learned that there was no P5 module related to a math topic or material, that students were not interested in learning on their own, and that pupils did not understand the concepts. (2) Design stage: During this phase, we produced prototype 1, which was the initial module design. (3) Development: The module is now in the valid category, and the module development trial is at the practical level. This process is based on how teachers and students responded to the module, how students responded to learning, observations of how the module was used, and results from learning outcome tests that showed how effective the module was. (4) Disseminate: At this stage, a summative evaluation is done to make sure that the module is useful and can improve learning outcomes. Next, they package the module and disseminate it.